(untitled) (Bangladesh Medical Journal, 2021)
Forcibly Displaced Myanmar Nationals (FDMN’s) specially Rohingya population considered as a maltreated minority. They suffered physical brutality that consequences are physical, sexual and psychological trauma. This community based cross-sectional study was carried out to ascertain the prevalence rate and associated factors of post traumatic stress disorder (PTSD) among the 363 adult Rohingyas in the Kutupalong and Nayapara refugee camps, Cox’s Bazar, Bangladesh by a semi-structured questionnaire through face-to-face interviews during the study period of June 2018 to November 2018. Among the 363 study participants, 60.33% had probable PTSD. The prevalence of PTSD was found higher in female (64.7%) in comparison to male (53.52%) and a statistically significant association (P=0.03) found between sex and PTSD. Married people had a higher prevalence of PTSD (64.62%) in compared to unmarried people and a significant association (P=0.003) found with the presence of PTSD. The prevalence of PTSD was very high (72.55%) among the respondents those faced sexual exploitation. Among the exploitations related variables, having previous experience of sexual exploitations were found statistically significant associated (P=0.039) with PTSD. Hypertension had a statistically significant association (P=0.02) with PTSD and the prevalence of PTSD among Hypertensive patients was 71.79%. Probable PTSD was highly prevalent among the Rohingya population in Bangladesh. Measures should be taken by trained healthcare professionals and mental healthcare providers. Bangladesh Med J. 2021 January; 50(1) : 39-45